Inovasi Sistem Pembelajaran PAI Berbasis Higher Order Thinking Skills (HOTS) di Pondok Pesantren Nurul Jadid Paiton Probolinggo - Sa’adah, Salamatus; Zainab, Iin; Wali, Muhammad; Suhermanto, Suhermanto (AFKARINA: Jurnal Pendidikan Agama Islam, 2022)
Abstract: The existence of this paper is to examine the Higher Order Thinking Skills (HOTS) applied at the Nurul Jadid Islamic Boarding School through a learning system that is internalized in the form of activities, programs and habituation patterns in Islamic boarding schools as an effort to shape the character of students, develop knowledge, insight, increase motivation , positive thinking, creative, critical and independent behavior. The method used in this research is qualitative research with a case study approach. Data collection techniques were carried out by interviews, observations and documentation. In this study the author intends to reveal how the PAI learning system based on Higher Order Thinking Skills (HOTS) is implemented at the Nurul Jadid Islamic boarding school. The results of this study are: Higher Order Thinking Skills (HOTS) Based Higher Order Thinking Skills (HOTS) Based PAI Learning System Innovations at the Nurul Jadid Paiton Islamic Boarding School, Probolinggo through habituation patterns, doctrinal patterns, Furudhul 'Ainiyah development, and organizational culture patterns.